Prediction of severe post-castration syndrome in women after surgical menopause - L.I. Butina; O.V. Olshevska; L.P. Shelestova; V.S. Olshevskyi (Publishing House TRILIST, 2022)
Objectives: prediction of severe post-castration syndrome (PCS) in women after surgical menopause. Materials and methods. The study included 67 surgically menopausal women aged 45-55 years who underwent surgical hysterectomy with or without appendages (the main group) and 30 naturally menopausal women (the comparison group). The method of constructing and analyzing multifactorial mathematical models was used to identify risk factors associated with the development of severe PCS in women after surgical menopause and assess its impact on the severity of PCS. 12 clinical and morphological factors were considered in the analysis. The severity of the PCS in women after surgical menopause was evaluated one month after surgery and symptoms of climacteric syndrome in women with natural menopause were assessed according to the modified Kupperman index. Results. Surgical menopause significantly increases the risk of severe PCS in comparison with natural menopause, when climacteric syndrome develops (p < 0.001). The risk of severe PCS increases with the removal of the uterine appendages, inflammatory changes in the uterine appendages, the ovarian cyst (p < 0.001), and uterine fibroids (p = 0.04). Three factor signs remain after selecting a set of independent signs in a multifactorial model for predicting the risk of severe PCS: removal of the uterine appendages (p < 0.001), inflammatory changes in the uterine appendages (p = 0.006), ovarian cyst (p = 0.082). Based on these factor signs, we can accurately predict the risk of severe PCS (AUC = 0.951, 95% CI 0.89-0.98). Conclusions. Women with surgical menopause after the uterine appendages removal, with inflammatory changes in the uterine appendages, and ovarian cysts are at risk for the development of severe PCS and therefore it is advisable for them to include in the complex treatment of PCS medicines which reduce inflammatory changes in the uterine appendages and restore immunological reactivity.